An investigation of the perceptions of laboratory animal welfare issues among undergraduate and graduate veterinary students in southeastern China - Yan, Shihong; Li, Hongyang; Lin, Jin; Chen, Huimin; Liu, Shasha; Diao, Hongxiu (Frontiers in Veterinary Science, 2024)
Animal experiments have played a significant role in advancing scientific knowledge and enhancing people's quality of life. In order to better understand the opinions and knowledge of veterinary students in the domain of laboratory animal welfare and to explore and advance the teaching methods used in animal ethics education, a questionnaire was designed and used to conduct a survey among undergraduate and postgraduate students majoring in veterinary medicine. The survey encompassed various topics, such as students' level of knowledge about animal welfare, their perspectives on laboratory animals, their proficiency with animal experiments, and their opinions on teaching methods and content. The respondents were a total of 150 undergraduate students and 148 graduate students. The survey results indicated that most students expressed a strong sense of responsibility for the safeguarding of the welfare of experimental animals. However, there were a few students who lacked compassion for animals. Additionally, there was a general lack of basic theoretical knowledge of animal ethics and an inadequate grasp of experimental techniques among current students. Furthermore, most of the participants expressed a strong sense of responsibility to advocate for animal welfare. Although a substantial number of students were unaware of the existence of agencies for the supervision of work involving laboratory animals, they supported teaching and supervision in the domain of animal welfare and were open to various teaching methods and topics of content. In conclusion, targeted training and education regarding laboratory animal welfare and ethics should be conducted in the future to address the specific needs of students. This study provides a foundation for future animal welfare education and will help to improve the professional skills and humanistic qualities of veterinary students.